2009
DOI: 10.1097/smj.0b013e3181b08c42
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Repeated Stool Toxin Testing for Diagnosing Clostridium difficile Colitis

Abstract: Clostridium difficile is diagnosed using the enzyme-linked immunoassay (EIA) with the specificity and sensitivity ranging from 50-90% and 70-95%, respectively. Due to the wide ranges, there is considerable confusion regarding the value of the EIA toxin test. We undertook this study to evaluate the benefit of repeat stool toxin testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In contrast to our results, the vast majority of commercial NAATs demonstrated high sensitivities in previous studies, but their high costs prevent their wide use 2,5,21 . At institutions where EIAs are still used for the diagnosis of CDI, some authors have suggested the submission of more than one sample from the same patient, but this practice remains controversial given that some studies have demonstrated that multiple samples do not signifi cantly increase the positive predictive value of the test and may even increase the rate of false positives 5,25,26 . Some authors have also suggested that an algorithm with at least two steps is required for the accurate diagnosis of CDI in humans, but there is still no consensus on which tests should be used in each step 5,16,22,27 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our results, the vast majority of commercial NAATs demonstrated high sensitivities in previous studies, but their high costs prevent their wide use 2,5,21 . At institutions where EIAs are still used for the diagnosis of CDI, some authors have suggested the submission of more than one sample from the same patient, but this practice remains controversial given that some studies have demonstrated that multiple samples do not signifi cantly increase the positive predictive value of the test and may even increase the rate of false positives 5,25,26 . Some authors have also suggested that an algorithm with at least two steps is required for the accurate diagnosis of CDI in humans, but there is still no consensus on which tests should be used in each step 5,16,22,27 .…”
Section: Discussionmentioning
confidence: 99%
“…13,43 47 Repeat testing during the same episode of diarrhea is discouraged, as there is limited yield. 48 50…”
Section: Diagnosismentioning
confidence: 99%
“…13,[43][44][45][46][47] Repeat testing during the same episode of diarrhea is discouraged, as there is limited yield. [48][49][50] Although the gold standard for laboratory testing is stool culture, which offers a high degree of sensitivity, most stool cultures take a minimum of 2 days, which may be prohibitive in critical situations. [51][52][53][54][55] Since 2009, the Food and Drug Administration (FDA) began to approve molecular platforms for direct detection of C difficile, including the BD GeneOhm Cdiff assay, the Xpert C difficile Epi assay, the Illumigene assay, and the AmpliVue C difficile assay, all of which have a sensitivity and specificity approaching 96% to 100%.…”
Section: Diagnosismentioning
confidence: 99%